Pendampingan terpadu UMKM kuliner dalam kegiatan sosial Manggala Sakti Sejahtera berbasis pemberdayaan ekonomi masyarakat - Abidillah Effendi; Apriliani Apriliani; Heru Cahyo; Edi Sumantri (Nur Science Institute, 2026)
Micro, Small, and Medium Enterprises (MSMEs) in the culinary sector have significant potential to support economic growth, particularly in generating employment opportunities, increasing income, and fostering local economic independence. However, the optimization of this potential is still constrained by several challenges, including limited access to capital, low production capacity, weak marketing strategies, income fluctuations, and inadequate supporting facilities and infrastructure. Therefore, an assistance program was conducted for culinary MSME actors in collaboration with Manggala Sakti Sejahtera, located in Kober Village, West Purwokerto District, Banyumas Regency. This assistance was implemented through a direct, participatory approach, using an integrated framework that includes identifying key problems, analyzing business needs, and evaluating program implementation. The program also focused on enhancing the capacity of business actors in production management, strengthening marketing strategies, and optimizing the use of available facilities and infrastructure. The results indicate that the integrated assistance program effectively improved business readiness, enhanced managerial practices, and significantly strengthened the sustainability and competitiveness of culinary MSMEs.